Norse revival: transformations of Germanic neopaganism - Schnurbein, Stefanie von (Studies in critical research on religion, 2016)
Preliminary Material -- Introduction -- Creating the Paradigm: Historical Preconditions of Modern Asatru -- Creating a Religion: The Emergence and Development of Late Twentieth Century Asatru -- Believing and Doing -- Contested Fields I: Race and Ethnicity -- Contested Fields II: Concepts of Religion and Anti-Monotheism -- Asatru – A Religion of Nature? -- Gender and Sexuality -- Asatru – An Academic Religion? -- Germanic Neopaganism – A Nordic Art-Religion? -- Instead of a Conclusion -- Interviews Conducted by Author -- Bibliography -- Index.